Photocatalytic mineralization of humic acids with TiO2: Effect of pH, sulfate and chloride anions - Jarek Wiszniowski; Didier Robert; Joanna Surmacz-Gorska; Korneliusz Miksch; Jean-Victor Weber (International Journal of Photoenergy)
Aims of the present work are to investigate the photomineralization of commercial humic acid in water solution.The effect of initial pH of solution and different anions (chloride, sulfate and mixture) on the photocatalytic degradation of HA with titanium dioxide in aqueous solution has been examined. The photocatalytic mineralization rate in alkaline solution is lower than in neutral and acidic solution. In our conditions no effect of chloride ions on the degradation rate is observed. The influence of the sulfate depends on its concentration in the solution. For a large concentration, we note a decrease of the mineralization rate.